KETAHANAN PANGAN RUMAH TANGGA PETANI PADI SAWAH PADA DAERAH RAWAN BANJIR (Suatu Kasus Desa Ciganjeng, Kecamatan Padaherang,Kabupaten Pangandaran) - Widhiguna, I Putu Sindhu Respati; Noor, Trisna Insan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Food security is a concept that describes the security level of stability of food availability, food accessibility, food consumption quality, and food continuity in one area. Household income is one of the most influential factors in order to fulfill the household food security needs. Farmer households in Ciganjeng Village experiences disruption in the level of income that they earn. The disruption is caused by the flood that occurred in their paddy fields, thus hamper the farmer household’s farming activities and creates economical pressure upon them. This study aims to analyze the level of food security aspects, and the level of the farmer household’s food security in Ciganjeng Village. This study uses quantitative approach with survey technique by using 74 respondents as sample. The result shows that 64,86% of the farmer household have stable  level of stability of food availability, 67,11% of the farmer household have direct access towards food, 100% of the farmer household have good food consumption quality, and most of the farmer household have low to very low level of food continuity in the amount of 35,14% and 18,92% for each level. These levels mainly affected by low level of farmer houshold’s consumption frequency, food supply patterns in each farmer households, also the status and habit on accessing food in each household.